Tributaries of modern Algerian literature and criticism (1925-1961 AD) - رهيوي, سليم (مجلة المخبر أبحاث في اللغة والأدب الجزائري; No 7 (2019): جامعة محمد خيضر بسكرة مجلة: '' المخبر أبحاث في اللغة والأدب الجزائري'' قسم الآداب واللغة العربية - جامعة بسكرة ، الجزائر, 2022)
(Opinions differed about the possibility of an Algerian monetary achievement in the period leading up to independence. And there are those who think that it does not amount to being called cash, because it lacks a methodological framework. Based on the foregoing, this paper examines an attempt to unmask those influences in the critical and literary achievement between 1925 and 1961 and to know the references of criticism and Algerian literature in that period. keywords ; Al-Naqat, Al-Dabiyah, Al Manhaj, Al-Rafid, Al-Modawana. (Opinions differed about the possibility of an Algerian monetary achievement in the period leading up to independence. And there are those who think that it does not amount to being called cash, because it lacks a methodological framework. Based on the foregoing, this paper examines an attempt to unmask those influences in the critical and literary achievement between 1925 and 1961 and to know the references of criticism and Algerian literature in that period. keywords ; Al-Naqat, Al-Dabiyah, Al Manhaj, Al-Rafid, Al-Modawana.